El despido intempestivo imperativo, en relación al cambio de ocupación del trabajador en el ecuador - Lastra Mercado, Eliceo (2016)
This research York on has been established to determine what effect involves the institution of summary dismissal in our Ecuadorian Labor Law, and thereby find most appropriate legal mechanisms that can help your better understanding and implementation by the administrators of justice, through the application of a precise definition to clarify its true nature scope, establishing specific causal, with the aim of which is supplied light and subjective interpretations of this atypical form of termination of employment at the individual and collective work. The labor code does not provide a clear and specific conceptualization about unfair dismissal, which is why most of the lawsuits filed by workers against their employers, are regarding this issue. Lack of laws and clarity in the matter, causes are regularly violated the fundamental rights of workers by their employers, leading to a large group of workers annually, remain dismissed from their jobs, which are forced to sue their former employers to compensate them, reaching settlement agreements to avoid labor disputes, which often does not justify the effort and the years of service on behalf of their employers. The aimwith thisresearchis to call for legal reform that contains a clear and precise concept of what is referred to summary dismissal, particularly causal point, where you should consider termination of a relationship labor as unfair dismissal, and thus to ensure the worker a better job stability and especially to be safeguarded in an appropriate manner the rights given to the working class.